The Influence of Social Media on Student Learning Behavior and Its Effects on Academic Achievement - Hamidah, Hamidah; okkita rizan (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2025)
The advancement of digital technology, particularly social media, has significantly transformed students’ learning behavior. The rapid digital transformation has significantly reshaped higher education, particularly in how students engage with academic content. This study aims to examine how social media usage influences students' learning behavior and its impact on academic performance, using a case study at the Institute of Science and Business (ISB) Atma Luhur. A descriptive quantitative approach was adopted, involving 150 students from various study programs. Data was collected through an online questionnaire covering the frequency of social media usage, types of learning activities conducted via social platforms, and students’ Grade Point Averages (GPA). The results reveal a significant shift in students' learning patterns, where platforms like WhatsApp, YouTube, and Instagram are utilized for sharing materials, group discussions, and seeking references. However, uncontrolled use negatively affects concentration and time management. Regression analysis shows a moderate positive correlation between academic-oriented social media use and improved performance, while excessive non-academic use correlates negatively with achievement. These findings highlight the importance of digital literacy and time management in optimizing the educational benefits of social media. The study recommends institutional policies that promote productive social media use and digital learning skill development among students. The results of this study obtained an R value of 0.456. This shows that 45.6% has an influence on the use of social media on student learning behavior and its impact on academic achievement, the remaining 54.4% is influenced by other factors not included in this research model.